2016
DOI: 10.1098/rspb.2016.2226
|View full text |Cite
|
Sign up to set email alerts
|

Sex as a strategy against rapidly evolving parasites

Abstract: Why is sex ubiquitous when asexual reproduction is much less costly? Sex disrupts coadapted gene complexes; it also causes costs associated with mate finding and the production of males who do not themselves bear offspring. Theory predicts parasites select for host sex, because genetically variable offspring can escape infection from parasites adapted to infect the previous generations. We examine this using a facultative sexual crustacean, Daphnia magna, and its sterilizing bacterial parasite, Pasteuria ramos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 35 publications
0
31
0
1
Order By: Relevance
“…However, this relies on the assumption that host genes that confer resistance to current parasites also confer resistance to future parasites (this is sometimes, though not always the case in this system: (Little & Ebert, 2001;Auld, Tinkler, & Tinsley, 2016 (Anderson et al, 1986;King & Lively, 2012). However, this relies on the assumption that host genes that confer resistance to current parasites also confer resistance to future parasites (this is sometimes, though not always the case in this system: (Little & Ebert, 2001;Auld, Tinkler, & Tinsley, 2016 (Anderson et al, 1986;King & Lively, 2012).…”
Section: Epidemic Size and Population Mixing Shape Host Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this relies on the assumption that host genes that confer resistance to current parasites also confer resistance to future parasites (this is sometimes, though not always the case in this system: (Little & Ebert, 2001;Auld, Tinkler, & Tinsley, 2016 (Anderson et al, 1986;King & Lively, 2012). However, this relies on the assumption that host genes that confer resistance to current parasites also confer resistance to future parasites (this is sometimes, though not always the case in this system: (Little & Ebert, 2001;Auld, Tinkler, & Tinsley, 2016 (Anderson et al, 1986;King & Lively, 2012).…”
Section: Epidemic Size and Population Mixing Shape Host Evolutionmentioning
confidence: 99%
“…year. However, this relies on the assumption that host genes that confer resistance to current parasites also confer resistance to future parasites (this is sometimes, though not always the case in this system: (Little & Ebert, 2001;Auld, Tinkler, & Tinsley, 2016 (Anderson et al, 1986;King & Lively, 2012). Moreover, a decline in genetic diversity reduces a population's capacity to respond to further selection more generally, because diversity is the currency with which a population pays for adaptation (Lande & Shannon, 1996).…”
Section: Epidemic Size and Population Mixing Shape Host Evolutionmentioning
confidence: 99%
“…Through decades of work, Lively et al have demonstrated that the population satisfies necessary conditions for the host-parasite coevolutionary dynamics and provides support for the hypothesis (e.g., Lively (1987Lively ( , 1989; Lively (1995b, 1998); Jokela et al (2009);Vergara et al (2014b); Gibson et al (2016)). While field studies often provide only indirect evidence for the hypothesis, experimental systems can be used to directly test the hypothesis (Auld et al, 2016;Slowinski et al, 2016;Lynch et al, 2018;Zilio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Daphnia provides a powerful model to study the importance of parasitism as a driver of evolution and disease; in fact, it has been used to understand the link between sex and parasites (Auld et al. ), multihost parasitism (Auld et al. ), and the virulence of human pathogens (Le Coadic et al.…”
mentioning
confidence: 99%
“…In particular, the short generation times of Daphnia (one to three weeks) coupled with the availability of isolated populations (with lakes representing closed study systems) facilitated the reconstruction of rapid coevolutionary dynamics. Therefore, Daphnia provides a powerful model to study the importance of parasitism as a driver of evolution and disease; in fact, it has been used to understand the link between sex and parasites (Auld et al 2016), multihost parasitism (Auld et al 2017), and the virulence of human pathogens (Le Coadic et al 2012). Using long-term, high-resolution records, Turko et al (2018) have shown that interactions between parasites and their hosts are not fixed in time but result from a dynamic battle of adaptation and counter-adaptation, as predicted by the Red Queen hypothesis.…”
mentioning
confidence: 99%